Albania in the Focus of World Press in Years 1970-1973 Man Directions on Assessment and Diplomatic Relations - Sallata, Ilir; Lazimi, Mirela (Mediterranean Journal of Social Sciences, 2012)
Albania's communist system coincides with the years 1944-1990.Albanian Communist Party victory of 1944 until the year1948 was oriented entirely toward Yugoslavia. It got away from the chauvinist policies of its malicious, closely related to the SovietUnion. To keep the "pure Marxist-Leninist line," PPSH broke with the Soviet Union in November 1961. The need for economicassistance and support in the field of foreign policy, the official Tirana looked forward China. The last one was considered as the mainally of our country, who supported the line of Marxism-Leninism. Although still early, a new wind of change was observed in theAlbanian-Chinese friendship. In early 1973 there is a deepening of the differences between the two allies. Relations with the SovietUnion continue to be tense and are slightly tempered by the socialist camp countries, friendly relations are Romania, Bulgaria, andHungary despite some ideological differences. We noticed the Balkan, a spirit of cooperation aiming easier and better neighborhood withYugoslavia and Greece. In this period, the communist government of West rejects demands for openness and collaboration by standingfirm in her line. Albania is not stopped short of linking diplomatic relations with several countries, mainly second-hand in the internationalarena.